2019
DOI: 10.7717/peerj.7951
|View full text |Cite
|
Sign up to set email alerts
|

Serum-deprived differentiated neuroblastoma F-11 cells express functional dorsal root ganglion neuron properties

Abstract: The isolation and culture of dorsal root ganglion (DRG) neurons cause adaptive changes in the expression and regulation of ion channels, with consequences on neuronal excitability. Considering that not all neurons survive the isolation and that DRG neurons are heterogeneous, it is difficult to find the cellular subtype of interest. For this reason, researchers opt for DRG-derived immortal cell lines to investigate endogenous properties. The F-11 cell line is a hybridoma of embryonic rat DRG neurons fused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Netrin-1 upregulated CGRP mRNA in F-11 cells (Guo et al, 2020). Recent studies also demonstrated that differentiated cells respond to SP with a small inward current (Pastori et al, 2019). Acidic solutions and acetylcholine, but neither capsaicin nor an agonists of the nociceptor-related mas-related gene (Mrg) receptors produced no effects in undifferentiated F-11 cells (Solinski et al, 2010;Yin et al, 2016;Pastori et al, 2019).…”
Section: B11mentioning
confidence: 99%
See 3 more Smart Citations
“…Netrin-1 upregulated CGRP mRNA in F-11 cells (Guo et al, 2020). Recent studies also demonstrated that differentiated cells respond to SP with a small inward current (Pastori et al, 2019). Acidic solutions and acetylcholine, but neither capsaicin nor an agonists of the nociceptor-related mas-related gene (Mrg) receptors produced no effects in undifferentiated F-11 cells (Solinski et al, 2010;Yin et al, 2016;Pastori et al, 2019).…”
Section: B11mentioning
confidence: 99%
“…Nevertheless, other factors have been shown to successfully differentiate the cells including nerve growth factor, NGF (Martin et al, 2002) and retinoic acid (Naruse et al, 1992). In addition to growth factors, low serum medium containing 1% FBS for about 2 weeks also promoted differentiation (Pastori et al, 2019) (Table 1). In the process of differentiation into a DRG neuron-like phenotype, these cells also change the glycosphingolipid profile that remains different to DRG neurons (Ariga et al, 1995).…”
Section: F-11 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological activity of neoglycosylated collagen matrices was evaluated with F-11 cells, a neuroblastoma cell line which proliferates in 10% serum medium but expresses electrophysiological properties of dorsal root ganglion (DRG) neurons under appropriate culture conditions [ 28 ]. F-11 was used as the cell line of choice because we previously demonstrated that it is able to generate functional neurons by its maintenance on neoglucosylated collagen matrices [ 16 ].…”
Section: Resultsmentioning
confidence: 99%